toner
The toner formulation addresses color unevenness by adjusting the SP value difference between resin and wax, and using silica fine particles treated with silicone oil, achieving improved image quality and charge stability.
Patent Information
- Application Number
- JP2021076275
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-04-28
AI Technical Summary
Existing toners with high wax content for low-temperature fixability suffer from color unevenness due to uneven crystallization of wax during fixing, leading to poor image quality.
A toner formulation with specific SP value differences between binder resin and wax, combined with silica fine particles surface-treated with silicone oil, ensures uniform wax crystallization on the toner surface, improving color uniformity and chargeability.
The toner maintains low-temperature fixability while significantly reducing color unevenness in fixed images, enhancing image quality and charge stability.
Smart Images

Figure 0007618496000001 
Figure 0007618496000002 
Figure 0007618496000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to toners for use in image forming processes such as electrophotography. [Background technology]
[0002] In recent years, there has been a demand for further energy saving in printers and copiers. In order to meet this demand, a toner that melts quickly at a lower temperature, i.e., a toner that has excellent low-temperature fixability, is preferred. In order to obtain a toner having excellent low-temperature fixability, for example, Patent Documents 1 and 2 have investigated the use of wax in the toner. The wax is added to the binder resin for the purpose of imparting plasticity to the binder resin. When the wax is melted and liquefied by heat, it becomes compatible with the binder resin, and the viscosity of the toner when melted decreases, making it possible to obtain a toner having excellent low-temperature fixability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-172744 A [Patent Document 2] JP 2019-086642 A Summary of the Invention [Problem to be solved by the invention]
[0004] As a result of the inventors' investigation, it was found that the toner according to Patent Document 1 contains a large amount of wax and has excellent low-temperature fixing properties, but the occurrence of color unevenness is an issue. That is, the binder resin in the toner particles and the wax become compatible with each other during fixing, so that the wax crystallizes unevenly after fixing, and color unevenness occurs in the fixed image.
[0005] In order to prevent the occurrence of color unevenness, it is necessary to crystallize the wax uniformly and quickly on the surface of the toner particles. In the toner according to Patent Document 2, a crystalline material that rapidly promotes crystal nucleation is added as a nucleating agent for the wax, thereby successfully increasing the crystallization speed of the wax. However, although the crystallization is promoted, there is still room for improvement in terms of uniformly crystallizing the wax, and there is still a need to improve the occurrence of color unevenness.
[0006] The present disclosure provides a toner that maintains low-temperature fixability, has excellent chargeability, and is improved in color unevenness of fixed images. [Means for solving the problem]
[0007] A toner comprising toner particles containing a binder resin and a wax, and inorganic fine particles on the surfaces of the toner particles, The binder resin contains resin A, The SP value of the resin A calculated by the Fedors method is SPa (cal / cm 3 ) 0.5 year, The SP value of the wax calculated by the Fedors method is SPw (cal / cm 3 ) 0.5 When The SPa and the SPw satisfy the following formula (1), 2.50≦SPa-SPw≦4.50 (1) the inorganic fine particles contain silica fine particles surface-treated with silicone oil, The silica fine particles 29 In Si-solid-state NMR measurements, The integral in D units calculated when the integral value in Q units in CP / MAS measurements is set to 100 Let the value be A, When the integral value in D units obtained when the integral value in Q units in DD / MAS measurement is 100 is B, The toner, wherein A and B satisfy the following formulae (2) and (3): 30≦B≦60 (2) 4.0≦A / B≦6.0 (3) Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a toner that maintains low-temperature fixability, has excellent chargeability, and has improved color unevenness in fixed images. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.
[0010] As described above, in order to improve color unevenness of a fixed image, it is necessary to uniformly and quickly crystallize the wax on the toner particle surface during fixing. In response to this, the present inventors believed that color unevenness could be improved if the wax could be uniformly exuded onto the toner particle surface during fixing and quickly crystallized on the toner particle surface, and as a result of extensive investigations, they arrived at the above toner.
[0011] The present disclosure relates to a toner comprising toner particles containing a binder resin and a wax, and inorganic fine particles on the surfaces of the toner particles, The binder resin contains resin A, The SP value of the resin A calculated by the Fedors method is SPa (cal / cm 3 ) 0.5 year, The SP value of the wax calculated by the Fedors method is SPw (cal / cm 3 ) 0.5 When The SPa and the SPw satisfy the following formula (1), 2.50≦SPa-SPw≦4.50 (1) the inorganic fine particles contain silica fine particles surface-treated with silicone oil, The silica fine particles 29 In Si-solid-state NMR measurements, The integral value in D units obtained when the integral value in Q units in the CP / MAS measurement is set to 100 is defined as A. When the integral value in D units obtained when the integral value in Q units in DD / MAS measurement is 100 is B, The toner is characterized in that A and B satisfy the following formulae (2) and (3). 30≦B≦60 (2) 4.0≦A / B≦6.0 (3)
[0012] In the course of their research, the inventors have found that by adjusting the value (SPa-SPw) obtained by subtracting the SP value of the wax from the SP value of the resin A to a range of 2.50 to 4.50, the wax will uniformly seep out onto the surface of the toner particles when the toner particles melt and deform during fixing. In addition, the inventors have found that by adjusting the value obtained by subtracting the SP value of the wax from the SP value of the resin A to a range of 2.50 to 4.50 and further adjusting the properties of the silica fine particles, the occurrence of color unevenness in the fixed image can be improved. The inventors consider the reason for this as follows.
[0013] By adjusting SPa-SPw to the above range, the wax that seeps out evenly onto the toner particle surface during fixing quickly adheres to the silicone oil present on the surface of the silica fine particles. This is considered to be because the SP value of the wax and the SP value of the silicone oil are close to each other, making them easy to blend. Next, during cooling after fixing, the molecular mobility of the wax decreases, and the crystallization of the wax progresses. At this time, if the molecular mobility of the silicone oil is high, the molecular mobility of the wax is less likely to decrease, and crystallization is likely to be inhibited. On the other hand, if the molecular mobility of the silicone oil is low, the molecular mobility of the wax is also likely to decrease, and crystallization is likely to be promoted. Therefore, by adjusting SPa-SPw to the above range, the wax is uniformly seeped out onto the toner particle surface during fixing, and the wax is more likely to adhere to the silicone oil surface of the silica fine particles. In addition, it is considered that the specific silicone oil makes it easier to proceed with the crystallization of the wax, thereby improving the occurrence of color unevenness in the fixed image.
[0014] As mentioned above, the unit of SPa-SPw (SP value is (cal / cm 3 ) 0.5 ) is greater than or equal to 2.50 and less than or equal to 4.50. When the value of SPa-SPw is less than 2.50, the wax and resin A are easily compatible with each other during fixing, so that the wax is easily inhibited from exuding uniformly onto the toner particle surface, resulting in color unevenness. When the value of SPa-SPw is more than 4.50, the wax and resin A are easily phase-separated during fixing, and the wax is easily integrated. As a result, the wax is easily inhibited from exuding uniformly onto the toner particle surface, resulting in color unevenness. In addition, when the value of SPa-SPw is more than 4.50, the wax exudes excessively onto the toner particle surface, resulting in a decrease in chargeability. SPa-SPw is preferably 2.90 or more and 4.00 or less, more preferably 3.00 or more and 3.60 or less.
[0015] Resin A is not particularly limited as long as it satisfies the above SP value difference, and known resins such as polyester resin, vinyl resin, epoxy resin, polyurethane resin, polyamide resin, cellulose resin, polyether resin, mixed resin or composite resin thereof can be used. The content of resin A in the toner particles is preferably 0.5% by mass or more, more preferably 3.0% by mass. When the content of resin A in the toner particles is within the above range, the wax is more easily exuded uniformly during fixing, and the occurrence of color unevenness can be further improved by combining with the function of the silicone oil described above. On the other hand, the upper limit of the content of resin A is not particularly limited, but it is preferably 80.0% by mass or less.
[0016] Resin A is preferably a polyester resin. When Resin A is a polyester resin, the wax is more likely to seep out uniformly onto the toner particle surface during fixing, and thus, by combining this with the function of the silicone oil described above, the occurrence of color unevenness can be further improved.
[0017] As the polyester resin, saturated polyester resin, unsaturated polyester resin, or both of them can be appropriately selected and used. As the polyester resin, a normal one produced from an alcohol component and an acid component can be used, and both components are exemplified below. As the dihydric alcohol component that can be used in the preparation of the polyester resin, ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, cyclohexanedimethanol, butenediol, octenediol, cyclohexenedimethanol, hydrogenated bisphenol A, bisphenol represented by formula (E) and its derivatives, and diols represented by formula (F), etc. can be mentioned. [ka] In formula (1), R represents an ethylene or propylene group. x and y each represent an integer of 0 or more, and the average value of x+y is 0 to 10. [ka] (In formula (2), R' represents any one of formulas (B1) to (B3). x' and y' are integers of 0 or more, and the average value of x'+y' is 0 to 10.)
[0018] In view of reactivity, it is preferable to use, for the polyester resin, bisphenol of formula (E) and derivatives thereof, or compounds of bisphenol of formula (E) and derivatives thereof in which the average value of x+y is 1 to 4.
[0019] Examples of trihydric or higher alcohols that can be used in the preparation of the polyester resin include glycerin, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0020] Additionally, other alcohol components that can be used in preparing the polyester resin include polyhydric alcohols such as, for example, oxyalkylene ethers of novolac-type phenolic resins.
[0021] Examples of divalent carboxylic acids that can be used in the preparation of polyester resins include benzenedicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, or their anhydrides, lower alkyl esters; alkyldicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or their anhydrides, lower alkyl esters; alkenylsuccinic acids or alkylsuccinic acids such as n-dodecenylsuccinic acid and n-dodecylsuccinic acid, or their anhydrides, lower alkyl esters; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid, or their anhydrides, lower alkyl esters; and dicarboxylic acids and derivatives thereof. In the present disclosure, benzenedicarboxylic acids such as terephthalic acid and isophthalic acid are preferably used from the viewpoint of handling and reactivity.
[0022] As a trivalent or higher polyvalent carboxylic acid component that can be used in the preparation of the polyester resin, For example, trimellitic acid, pyromellitic acid, 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, empol trimer acid, and their anhydrides, lower alkyl esters; tetracarboxylic acids represented by formula (G), and their anhydrides, lower alkyl esters, and other polyvalent carboxylic acids and their derivatives. Trimellitic acid is preferably used from the viewpoint of reactivity and ease of adjusting the resin acid value. [ka] (In formula (G), X represents an alkylene group or an alkenylene group. However, X is a substituent having 5 to 30 carbon atoms and one or more side chains having 3 or more carbon atoms.)
[0023] Further, other acid components that can be used in the preparation of the polyester resin include polycarboxylic acids such as 1,2,3,4-butanetetracarboxylic acid, benzophenonetetracarboxylic acid and their anhydrides.
[0024] From the viewpoint of electrostatic chargeability, the SP value (SPa) of the resin A is preferably 10.50 or more and 12.80 or less, and more preferably 11.00 or more and 12.60 or less. When the SPa is in the above range, an appropriate amount of moisture is adsorbed to the resin A, and the electrostatic chargeability is easily improved.
[0025] In order to increase SPa, resin A preferably has a monomer unit represented by the following formula (A) in the resin structure. By incorporating a highly hydrophilic unit such as the monomer unit represented by formula (A) into resin A, SPa is increased and phase separation with the wax can be further improved. As a result, uniform exudation of the wax onto the toner particle surface during fixing is easily promoted, and by combining this with the action of silicone oil, the occurrence of color unevenness can be further improved. The monomer unit refers to a form in which a monomer substance in a polymer is reacted. The content (mass %) of the monomer unit represented by formula (A) in resin A is preferably 0 mass % or more and 20 mass % or less. [ka]
[0026] When a polyester resin having a monomer unit represented by formula (A) is used as resin A, it may be prepared by condensing a divalent carboxylic acid or its anhydride with isosorbide represented by the following formula (H). Specifically, it may be prepared by a method of dehydration condensation at a reaction temperature of 180 to 260°C in a nitrogen atmosphere in a composition ratio that leaves a carboxy group. Cut. [ka]
[0027] The weight average molecular weight (Mw) of Resin A is not particularly limited, but is preferably 5,000 to 50,000, and more preferably 8,000 to 20,000.
[0028] The type of wax is not particularly limited, and the following known materials can be used. Esters of monohydric alcohols and aliphatic monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate, or esters of monohydric carboxylic acids and aliphatic monoalcohols; esters of dihydric alcohols and aliphatic monocarboxylic acids, such as dibehenyl sebacate and hexanediol dibehenate, or esters of dihydric carboxylic acids and aliphatic monoalcohols; esters of trihydric alcohols and aliphatic monocarboxylic acids, such as glycerin tribehenate, or esters of trihydric carboxylic acids and aliphatic monoalcohols; esters of tetrahydric alcohols and aliphatic monocarboxylic acids, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate, or esters of tetrahydric carboxylic acids and aliphatic monoalcohols; esters of hexahydric alcohols, such as dipentaerythritol hexastearate and dipentaerythritol hexapalmitate, Esters of aliphatic monocarboxylic acids, or esters of hexavalent carboxylic acids and aliphatic monoalcohols; esters of polyhydric alcohols such as polyglycerin behenate and aliphatic monocarboxylic acids, or esters of polyhydric carboxylic acids and aliphatic monoalcohols; natural ester waxes such as carnauba wax and rice wax (all of the above are also simply referred to as ester waxes); petroleum-based waxes and their derivatives such as paraffin wax, microcrystalline wax, petrolatum, etc.; hydrocarbon waxes and their derivatives produced by the Fischer-Tropsch method; polyolefin waxes and their derivatives such as polyethylene wax and polypropylene wax (all of the above are also simply referred to as hydrocarbon waxes); fatty acids such as higher aliphatic alcohols, stearic acid, palmitic acid, etc.; acid amide waxes; and low molecular weight crystalline polyesters such as diethylene glycol distearate.
[0029] The wax preferably contains at least one selected from the group consisting of the ester wax and the hydrocarbon wax, and more preferably uses one of the ester wax and the hydrocarbon wax. From the viewpoint of low-temperature fixability and durability, the content of the wax is preferably 3.0 parts by mass to 25.0 parts by mass, and more preferably 10.0 parts by mass to 25.0 parts by mass, relative to 100 parts by mass of the binder resin. The SP value (SPw) of the wax is preferably 7.90 or more and 9.60 or less, more preferably 7.90 or more and 9.20 or less, and even more preferably 8.00 or more and 9.00 or less.
[0030] The inorganic fine particles contain silica fine particles that have been surface-treated with silicone oil. In other words, the inorganic fine particles contain silica fine particles, and the silica fine particles are surface-treated with silicone oil. 29 In Si-solid-state NMR measurement, when the integral value of the D unit obtained when the integral value of the Q unit in the CP / MAS measurement is set to 100 is defined as A, and the integral value of the D unit obtained when the integral value of the Q unit in the DD / MAS measurement is set to 100 is defined as B, it is necessary that A and B satisfy the following formulas (2) and (3). 30≦B≦60 (2) 4.0≦A / B≦6.0 (3)
[0031] In the formulas (2) and (3), A and B are 29 Calculated by Si-solid state NMR. 29 In Si solid-state NMR, four types of peaks can be observed for silicon atoms in a solid sample: M unit (formula (4)), D unit (formula (5)), T unit (formula (6)), and Q unit (formula (7)). M units: (Ri)(Rj)(Rk)SiO 1 / 2 Formula (4) D unit: (Rg)(Rh)Si(O 1 / 2 )2 formula (5) T units: RmSi(O 1 / 2 )3 formula (6) Q unit: Si(O 1 / 2 )4 formula (7) (In the formulas (4), (5), and (6), Ri, Rj, Rk, Rg, Rh, and Rm each represent an alkyl group such as a hydrocarbon group having 1 to 6 carbon atoms, a halogen atom, a hydroxyl group, an acetoxy group, or an alkoxy group bonded to a silicon atom.)
[0032] 29 In the Si-solid-state NMR measurement, two types of measurement methods are used: DD / MAS measurement method and CP / MAS measurement method. In the DD / MAS measurement method, all silicon atoms in the measurement sample are observed, so information on the content of silicon atoms can be obtained. When silica fine particles are measured by DD / MAS, the Q unit indicates a peak derived from the silica fine particles before surface treatment (hereinafter also referred to as silica base material), and the D unit indicates a peak derived from the silicone oil, which is a surface treatment agent. In other words, the integral value of the D unit obtained when the integral value of the Q unit is set to 100 in the formula (2), B in the formula (2), that is, the amount of silicone oil present in the silica fine particles. For example, the more silicone oil present on the surface of the silica base material, the larger the value of B becomes.
[0033] On the other hand, in CP / MAS measurements, since measurements are made while being magnetized through hydrogen atoms present near silicon atoms, silicon atoms present near hydrogen atoms can be observed with good sensitivity. The presence of hydrogen atoms near silicon atoms means that the molecular mobility of the measurement sample is low. In other words, the lower the molecular mobility of the measurement sample and the greater the amount of hydrogen atoms, the more sensitively silicon atoms can be observed. In other words, when silica fine particles are measured by CP / MAS, the integral value of D units obtained when A in formula (3), that is, the integral value of Q units, is set to 100, contains not only the amount of silicone oil relative to the silica base material, but also information about the molecular mobility of the silicone oil. For example, the more silicone oil with low molecular mobility is present on the silica base material surface, the larger the value of A will be. Therefore, by calculating A / B, which is the standard value obtained by dividing A by B, information about the molecular mobility of the silicone oil present on the silica base material surface can be obtained appropriately. Here, A / B means that the larger the value of A / B, the lower the molecular mobility of the silicone oil.
[0034] When B is 30 or less, the silica fine particles are sufficiently surface-treated with the silicone oil, and the silicone oil is hydrophobic, so that the chargeability in a high-temperature and high-humidity environment is improved. On the other hand, when B is 60 or less, the disintegration property of the silica fine particles is improved, and when the silica fine particles are externally added to the toner particles, the silica fine particles are easily uniformly fixed to the toner particles, and the chargeability is improved. B is preferably 35 or more and 55 or less. B can be controlled by the amount of treatment with the silicone oil and the number-average particle size of the silica raw material.
[0035] When A / B is less than 4.0, the molecular mobility of the silicone oil present on the surface of the silica base material is high, so the molecular mobility of the wax is difficult to decrease, the crystallization of the wax is inhibited, and color unevenness occurs. On the other hand, when A / B is more than 6.0, the molecular mobility of the silicone oil becomes too low, so the frequency of the wax adhering to the silicone oil decreases. As a result, it becomes difficult to decrease the molecular mobility of the wax, the crystallization of the wax is inhibited, and color unevenness occurs. A / B is preferably 4.7 or more and 5.7 or less. In addition, A / B is preferably 4.7 or more and 5.7 or less. This can be controlled by changing the substituents on the oil side chains and ends, and by the amount of silicone oil treated.
[0036] As the silica raw material, which is the silica fine particles before surface treatment, known materials can be used.For example, silicon compounds, particularly silicon halides, generally silicon chlorides, fumed silica produced by burning purified silicon tetrachloride in oxyhydrogen flame, wet silica produced from water glass, sol-gel silica particles obtained by wet method, gel silica particles, aqueous colloidal silica particles, alcoholic silica particles, fused silica particles obtained by gas phase method, deflagration silica particles, etc. can be mentioned.
[0037] The inorganic fine particles contain silica fine particles, and the silica fine particles are surface-treated silica fine particles before surface treatment with silicone oil, and the number-average particle size of the primary particles of the silica fine particles before surface treatment is preferably 5 nm or more and 35 nm or less, and more preferably 5 nm or more and 30 nm or less. When the particle size is within the above range, the toner can be sufficiently given high fluidity and high chargeability. Also, when the particle size is within the above range, the above B and A / B can be easily adjusted.
[0038] Examples of silicone oils (surface treatment agents) include known silicone oils such as dimethyl silicone oil (polysiloxane in which all side chains and terminals are methyl groups) and modified silicone oils in which the methyl groups in the side chains or molecular chain terminals of dimethyl silicone oil are substituted with functional groups such as hydrogen atoms, phenyl groups, carbinol groups, hydroxyl groups, carboxyl groups, and epoxy groups.
[0039] The inorganic fine particles contain silica fine particles, and the silica fine particles are surface-treated products obtained by surface-treating the silica fine particles before surface treatment with silicone oil, and the amount of silicone oil is preferably 15.0 parts by mass or more and 40.0 parts by mass or less, and more preferably 23.0 parts by mass or more and 35.0 parts by mass or less, relative to 100 parts by mass of the silica fine particles before surface treatment.When the amount is 15.0 parts by mass or more, the silica fine particles are sufficiently surface-treated with silicone oil, and since silicone oil has hydrophobicity, the chargeability in a high-temperature and high-humidity environment is easily improved.On the other hand, when the amount is 40.0 parts by mass or less, the disintegration property of the silica fine particles is improved, and when the silica fine particles are externally added to the toner particles, the silica fine particles are easily fixed uniformly to the toner particles, and the chargeability is easily improved.
[0040] In addition, it is preferable that the silicone oil contains modified silicone oil.When the silicone oil contains modified silicone oil, the modified silicone oil is firmly fixed to the surface of the silica fine particles (that is, the silica base material) before surface treatment, so that the molecular mobility of the silicone oil is easily reduced.Therefore, when fixing, the wax crystallization is easily caused by the modified silicone oil, and by combining with the uniform exudation effect of the wax described above, the occurrence of color unevenness is easily improved.
[0041] In addition, the silicone oil preferably contains the modified silicone oil represented by formula (B). The modified silicone oil is a modified silicone oil having a reactive group at the molecular chain end (one end or both ends) of dimethyl silicone oil. The modified silicone oil having a reactive group at the molecular chain end forms a chemical bond with the silanol group on the surface of the silica base material at the molecular chain end, so that it is easy to reduce the molecular mobility of the silicone oil. As a result, it is easy to promote the crystallization of the wax, and by combining with the above-mentioned uniform exudation effect of the wax, it is easy to improve the occurrence of color unevenness. [ka] (In the formula, R 1 R is a carbinol group, a hydroxyl group, an epoxy group, a carboxyl group, an alkyl group, or a hydrogen atom. 2 is a carbinol group, a hydroxy group, an epoxy group, a carboxy group, or a hydrogen atom. m is an integer of 30 to 200 (more preferably 40 to 100). The alkyl groups on the side chain in formula (B) may each be substituted with a carbinol group, a hydroxy group, an epoxy group, a carboxy group, or a hydrogen atom.
[0042] In addition, the silicone oil preferably contains the modified silicone oil represented by formula (C). The modified silicone oil represented by formula (C) is a modified silicone oil having hydroxyl groups at both ends of the molecular chain. The hydroxyl groups present at the molecular chain ends of the modified silicone oil form strong siloxane bonds with the silanol groups on the surface of the silica base material, so that the molecular mobility of the silicone oil is easily reduced. Therefore, the crystallization of the wax is easily advanced, and by combining with the uniform exudation effect of the wax described above, the occurrence of color unevenness is easily improved. [ka] (In the formula, p is an integer of 30 to 200 (more preferably 40 to 100).)
[0043] The silicone oil preferably further contains polydimethylsiloxane represented by the following formula (D). When the silicone oil contains polydimethylsiloxane represented by formula (D) and the modified silicone oil, the silica fine particles are sufficiently hydrophobized, and the chargeability is easily improved. In addition, the B and A / B are easily adjusted to the above ranges. The amount of polydimethylsiloxane represented by formula (D) to be treated is preferably 12.0 parts by mass or more and 35.0 parts by mass or less, and more preferably 12.0 parts by mass or more and 27.0 parts by mass or less, relative to 100 parts by mass of the silica fine particles before surface treatment. [ka] (In the formula, n is an integer of 30 to 200 (more preferably 40 to 100).)
[0044] The amount of the modified silicone oil to be treated is preferably 0.2 parts by mass or more and 15.0 parts by mass or less, and more preferably 1.0 parts by mass or more and 13.0 parts by mass or less, relative to 100 parts by mass of the silica fine particles before surface treatment. By setting the amount of treatment within the above range, it becomes easier to adjust the B and A / B to the above range. The content of the silica fine particles surface-treated with silicone oil is preferably 0.2 parts by mass or more and 15.0 parts by mass or less, and more preferably 0.5 parts by mass or more and 13.0 parts by mass or less, relative to 100 parts by mass of the toner particles.
[0045] The surface treatment of the silica raw material with silicone oil can be carried out by a known wet method or dry method. By using these methods, the surface treatment can be carried out under a state in which the silica raw material is dispersed so that the aggregate diameter of the silica fine particles is mechanically appropriate. In addition, in the surface treatment with silicone oil, the above-mentioned silicone oil may be used alone or in combination. Furthermore, when using multiple types, after the treatment step 1 with the first treatment agent in which the silica raw material is treated with the first silicone oil, the treatment step 2 with the second treatment agent in which the silica raw material is treated with the second silicone oil may be carried out. When there are multiple treatment steps, the above B and A / B can be adjusted to the above range more delicately.
[0046] The binder resin may be a known one. For example, homopolymers of styrene and its substitutes, such as polystyrene and polyvinyltoluene; styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-dimethylaminoethyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-dimethylaminoethyl methacrylate copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-maleic acid copolymer, and styrene-maleic acid ester copolymer; polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resin, polyester resin, polyamide resin, epoxy resin, or polyacrylic acid resin may be used alone or in combination. Among these, styrene-acrylic resins, typically styrene-butyl acrylate, and polyester resins are particularly preferred in terms of developing properties, fixing properties, and the like.
[0047] Examples of the polymerizable monomer that forms the styrene-acrylic resin include the following: The styrene-based polymerizable monomer includes styrene; α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, and p-methoxystyrene.
[0048] Examples of the acrylic polymerizable monomer include acrylic polymerizable monomers such as methyl acrylate, ethyl acrylate, n-propyl acrylate, iso-propyl acrylate, n-butyl acrylate, iso-butyl acrylate, tert-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, and cyclohexyl acrylate.
[0049] Examples of the methacrylic polymerizable monomer include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, iso-propyl methacrylate, n-butyl methacrylate, iso-butyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, and n-octyl methacrylate. The method for producing the styrene-acrylic resin is not particularly limited, and known methods can be used.
[0050] Examples of the polymerizable monomer that forms the polyester resin include the following. The polyester resin may be, for example, a condensation polymer of a polycarboxylic acid and a polyhydric alcohol. The polyester resin may be a commercially available product or a synthesized product.
[0051] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids.
[0052] The polyvalent carboxylic acid may be used in combination with a dicarboxylic acid and a trivalent or higher carboxylic acid having a crosslinked or branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower alkyl esters thereof (e.g., carbon number 1 to 5). The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0053] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols.
[0054] As the polyhydric alcohol, a trihydric or higher polyhydric alcohol having a crosslinked structure or a branched structure may be used in combination with the diol. Examples of the trihydric or higher polyhydric alcohol include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohol may be used alone or in combination of two or more. The method for producing the polyester resin is not particularly limited, and a known method may be used. The binder resin may also be used in combination with other known resins.
[0055] The toner particles may contain a colorant. Examples of the colorant include the following organic pigments, organic dyes, and inorganic pigments. Examples of the yellow pigment include monoazo compounds. , disazo compounds, condensed azo compounds, isoindolinone compounds, isoindoline compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, and 185.
[0056] Examples of magenta pigments include monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet 19.
[0057] Examples of cyan pigments include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.
[0058] Examples of black pigments include carbon black, aniline black, non-magnetic ferrite, magnetite, etc. Also, pigments toned to black using the above yellow pigments, magenta pigments, and cyan pigments may be used.
[0059] Furthermore, the toner of the present disclosure can be made into a magnetic toner by incorporating a magnetic material. In this case, the magnetic material can also serve as a colorant. Examples of the magnetic material include iron oxides such as magnetite, hematite, and ferrite; alloys with metals such as iron, aluminum, copper, magnesium, tin, zinc, antimony, beryllium, bismuth, cadmium, calcium, manganese, selenium, titanium, tungsten, and vanadium, and mixtures thereof.
[0060] These pigments may be hydrophobized by a known method. These pigments may be used alone or in mixture, or in the form of a solid solution. Various dyes conventionally known as colorants may be used in combination with the pigment. The content of the pigment is preferably 1.0 to 20.0 parts by mass per 100.0 parts by mass of the binder resin.
[0061] The toner particles may further contain a charge control agent. As the charge control agent, a conventionally known charge control agent can be used without any particular limitation. As the charge control agent, there are a negative charge control agent that controls the toner to be negatively charged, and a positive charge control agent that controls the toner to be positively charged. Specifically, as the negative charge control agent, there are metal complexes of aromatic carboxylic acids represented by salicylic acid, alkyl salicylic acid, dialkyl salicylic acid, naphthoic acid, dicarboxylic acid, etc., polymers or copolymers having sulfonic acid groups, sulfonate groups, or sulfonate ester groups, metal salts or metal complexes of azo dyes or azo pigments, boron compounds, silicon compounds, calixarenes, etc. On the other hand, as the positive charge control agent, there are quaternary ammonium salts, polymeric compounds having quaternary ammonium salts in the side chains, guanidine compounds, nigrosine compounds, imidazole compounds, etc. As the polymer or copolymer having a sulfonic acid group, a sulfonate group or a sulfonate ester group, a homopolymer of a vinyl monomer containing a sulfonic acid group, such as styrene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-methacrylamido-2-methylpropanesulfonic acid, vinyl sulfonic acid, methacrylsulfonic acid, etc., or a copolymer of a vinyl monomer listed in the section on binder resin and the above-mentioned vinyl monomer containing a sulfonic acid group, etc., can be used. The amount of the charge control agent to be added is preferably 0.01 parts by mass or more and 20.0 parts by mass or less relative to 100.0 parts by mass of the binder resin. stomach.
[0062] In addition to the silica fine particles described above, the inorganic fine particles may be used in combination with the following inorganic fine particles. Titanium oxide, carbon black, carbon fluoride, metal oxides (e.g., strontium titanate, cerium oxide, alumina, magnesium oxide, chromium oxide), nitrides (e.g., silicon nitride), metal salts (e.g., calcium sulfate, barium sulfate, calcium carbonate), and fatty acid metal salts (e.g., zinc stearate, calcium stearate). The inorganic fine particles may be hydrophobized to improve the fluidity of the toner and to uniformly charge the toner particles. Examples of the treatment agent for hydrophobizing the inorganic fine particles include unmodified silicone varnish, various modified silicone varnishes, unmodified silicone oil, silane compounds, silane coupling agents, other organic silicon compounds, and organic titanium compounds, in addition to the modified silicone oil described above. These treatment agents may be used alone or in combination. The content of the inorganic fine particles is preferably 0.2 parts by mass or more and 15.0 parts by mass or less, and more preferably 0.5 parts by mass or more and 13.0 parts by mass or less, relative to 100 parts by mass of the toner particles.
[0063] The toner particles may be produced by either a dry method (e.g., kneading and grinding method, etc.) or a wet method (e.g., emulsion aggregation method, suspension polymerization method, etc.). When produced by the kneading and grinding method, for example, binder resin containing resin A and wax, and materials such as colorant and charge control agent as necessary are thoroughly mixed by a mixer such as a Henschel mixer or a ball mill. Thereafter, the toner materials are dispersed or dissolved by melting and kneading using a thermal kneader such as a heating roll, kneader, or extruder, cooled and solidified, pulverized, classified, and surface-treated as necessary to obtain toner particles. The order of classification and surface treatment does not matter. In the classification step, it is preferable to use a multi-division classifier in terms of production efficiency.
[0064] The emulsion aggregation method is a method of producing toner by preparing in advance an aqueous dispersion of fine particles made of the constituent materials of toner particles that are sufficiently small relative to the desired particle size, agglomerating the fine particles in an aqueous medium until they reach the toner particle size, and fusing the resin by heating. That is, in the emulsion aggregation method, toner particles are manufactured through a dispersion process in which a fine particle dispersion liquid consisting of the constituent materials of the toner particles is prepared, an aggregation process in which the fine particles consisting of the constituent materials of the toner particles are aggregated and the particle diameter is controlled until the particle diameter becomes the toner particle diameter, a fusion process in which the resin contained in the obtained aggregated particles is fused, and a subsequent cooling process.
[0065] The suspension polymerization method is a method in which a polymerizable monomer composition is obtained by uniformly dissolving or dispersing a polymerizable monomer, a binder resin containing resin A, and a wax (and, if necessary, a colorant, a polymerization initiator, a crosslinking agent, a charge control agent, and other additives). This polymerizable monomer composition is then dispersed in a continuous layer (e.g., an aqueous phase) containing a dispersant using an appropriate stirrer, and a polymerization reaction is simultaneously carried out to obtain toner particles having a desired particle size. The toner particles obtained by this suspension polymerization method (hereinafter also referred to as "polymerized toner particles") have an almost uniform spherical shape, and therefore the distribution of the charge amount is relatively uniform, and therefore improvement in image quality can be expected.
[0066] In the production of polymerized toner particles, examples of the polymerizable monomer that constitutes the polymerizable monomer composition include the following: styrene-based monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, and p-ethylstyrene; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, n-propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate, and phenyl acrylate; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, dodecyl methacrylate, 2-ethylhexyl methacrylate, and stearyl methacrylate; methacrylic acid esters such as acrylonitrile, phenyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, etc.; and other monomers such as acrylonitrile, methacrylonitrile, acrylamide, etc. These monomers may be used alone or in combination. Among the above-mentioned monomers, it is preferable to use styrene alone or in combination with other monomers in terms of the development characteristics and durability of the toner.
[0067] The polymerization initiator used in the production by the suspension polymerization method is preferably one having a half-life of 0.5 to 30 hours during the polymerization reaction. When the polymerization reaction is carried out using an addition amount of 0.5 to 20 parts by mass per 100 parts by mass of the polymerizable monomer, a polymer having a maximum molecular weight between 5,000 and 50,000 can be obtained, and the toner particles can be provided with desirable strength and suitable melting properties.
[0068] Examples of the polymerization initiator include azo or diazo polymerization initiators such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile; and peroxide polymerization initiators such as benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, t-butyl peroxy 2-ethylhexanoate, and t-butyl peroxypivalate.
[0069] When the toner particles are produced by the suspension polymerization method, a crosslinking agent may be added. By adding the crosslinking agent, the viscosity of the toner particles at 120° C. can be increased. The preferred amount of the crosslinking agent to be added is 0.001 to 15 parts by mass with respect to 100 parts by mass of the polymerizable monomer.
[0070] As the crosslinking agent, a compound having two or more polymerizable double bonds is mainly used, for example, aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene, etc.; carboxylic acid esters having two double bonds such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, etc.; divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide, divinyl sulfone, etc.; and compounds having three or more vinyl groups. These are used alone or as a mixture of two or more kinds.
[0071] When toner particles are produced by the suspension polymerization method, the above-mentioned toner composition and the like are generally appropriately added, and the polymerizable monomer composition is uniformly dissolved or dispersed by a dispersing machine such as a homogenizer, a ball mill, or an ultrasonic dispersing machine, and then suspended in an aqueous medium containing a dispersing agent. At this time, the particle size of the obtained toner particles is sharper if a high-speed dispersing machine such as a high-speed stirrer or an ultrasonic dispersing machine is used to make the toner particles into the desired size at once. The timing of adding the polymerization initiator may be added at the same time as adding other additives to the polymerizable monomer, or it may be mixed just before suspending in the aqueous medium. In addition, the polymerization initiator dissolved in the polymerizable monomer or solvent may be added just after granulation and before starting the polymerization reaction. After granulation, a normal stirrer may be used to stir the particles to an extent that the particle state is maintained and the particles are prevented from floating or settling.
[0072] When producing toner particles, known surfactants, organic dispersants, and inorganic dispersants can be used as dispersants. Among them, inorganic dispersants are preferably used because they are less likely to produce harmful ultrafine powders, and because their dispersion stability is achieved by their steric hindrance, stability is not easily lost even when the reaction temperature is changed, and they are easy to wash and do not adversely affect the toner particles. Examples of inorganic dispersants include polyvalent metal phosphates such as tricalcium phosphate, magnesium phosphate, aluminum phosphate, zinc phosphate, and hydroxyapatite, carbonates such as calcium carbonate and magnesium carbonate, and metasilica. Examples of the inorganic salts include calcium hydroxide, calcium sulfate, and barium sulfate, and inorganic compounds such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide.
[0073] The inorganic dispersant is preferably used in an amount of 0.2 to 20 parts by mass based on 100 parts by mass of the polymerizable monomer. The dispersant may be used alone or in combination of two or more kinds. Furthermore, 0.001 to 0.1 parts by mass of a surfactant may be used in combination.
[0074] When using these inorganic dispersants, they may be used as they are, but in order to obtain finer particles, the inorganic dispersant particles may be formed in an aqueous medium and used. For example, in the case of tricalcium phosphate, a sodium phosphate aqueous solution and a calcium chloride aqueous solution are mixed under high speed stirring to form water-insoluble calcium phosphate, which allows for more uniform and fine dispersion. At the same time, a water-soluble sodium chloride salt is by-produced, but if a water-soluble salt is present in the aqueous medium, the dissolution of the polymerizable monomer in water is suppressed, making it difficult to generate ultrafine toner particles by emulsion polymerization, which is more convenient.
[0075] Examples of the surfactant include sodium dodecylbenzene sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, sodium stearate, and potassium stearate.
[0076] In the step of polymerizing the polymerizable monomer, the polymerization temperature is set to 40°C or higher, generally 50 to 90°C.
[0077] The obtained polymer particles are filtered, washed, and dried by a known method to obtain toner particles. The toner particles are externally added and mixed with inorganic fine particles containing silica fine particles surface-treated with silicone oil to adhere to the surface of the toner particles, thereby obtaining the toner of the present disclosure. It is also possible to insert a classification process into the manufacturing process (before mixing with inorganic fine powder) to remove coarse powder and fine powder contained in the toner particles.
[0078] The mixing method may be any known method, for example, a Henschel mixer.
[0079] Next, methods for measuring various physical properties related to the toner of the present disclosure will be described. (Measuring the melting point of wax) The melting point of the wax is measured in accordance with ASTM D3418-82 using a differential scanning calorimeter "Q2000". The melting points of indium and zinc are used for temperature correction of the detector, and the heat of fusion of indium is used for heat correction. Specifically, 1.0 mg of wax is precisely weighed and placed in an aluminum pan. An empty aluminum pan is used as a reference, and the measurement is performed at a temperature rise rate of 10°C / min in the measurement temperature range of 30 to 200°C. In the measurement, the temperature is raised to 200°C at a temperature rise rate of 10°C / min, then cooled to 30°C at a temperature drop rate of 10°C / min, and then heated again. The peak temperature (unit: °C) of the maximum endothermic peak of the DSC curve in the temperature range of 30 to 200°C during this second heating process is taken as the melting point of the wax in the DSC measurement.
[0080] (Measurement of weight average particle size (D4) and number average particle size (D1) of toner (particles) or silica base material) The weight-average particle size (D4) and number-average particle size (D1) of the toner (particles) were measured using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3" for setting measurement conditions and analyzing measurement data. Measurements are made using a Beckman Coulter Multisizer 3 Version 3.51 (Beckman Coulter) with an effective measurement channel count of 25,000, and the measurement data is analyzed and calculated. The electrolyte solution used for the measurements is made by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, ISOTON II (Beckman Coulter). Before performing the measurements and analysis, the dedicated software is set up as follows.
[0081] In the "Change Standard Measurement Method (SOM) Screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (manufactured by Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. Also, set the current to 1600 μA, the gain to 2, the electrolyte solution to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bin, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows.
[0082] (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) Approximately 30 ml of the above-mentioned aqueous electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A predetermined amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) or number average particle size (D1) is calculated. Note that when the dedicated software is set to Graph / Volume %, the "Arithmetic diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight average particle size (D4), and when the dedicated software is set to Graph / Number %, the "Arithmetic diameter" on the Analysis / Number Statistics (Arithmetic Mean) screen is the number average particle size (D1).
[0083] (Method for measuring molecular weight of wax and resin A) The molecular weights of the wax and resin A are measured by gel permeation chromatography (GPC) as follows. First, a sample is dissolved in tetrahydrofuran (THF) at room temperature. The resulting solution is then filtered through a solvent-resistant membrane filter "Maeshori Disk" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution contains only the components soluble in THF. Adjust to a concentration of 0.8 mass%. Using this sample solution, measure under the following conditions. Apparatus: High-speed GPC apparatus "HLC-8220GPC" [manufactured by Tosoh Corporation] Column: Two connected LF-604 Eluent: THF Flow rate: 0.6 ml / min Oven temperature: 40 °C Sample injection volume: 0.020 ml
[0084] When calculating the molecular weight of the sample, use the molecular weight calibration curve prepared using a standard polystyrene resin (for example, trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation).
[0085] <Method for Measuring SP Value> The SP value used in the invention is calculated from the types and ratios of the monomers constituting the resin by the generally used Fedors method. From the table described in [polym. Eng. Sci., 14(2) 147-154(1974)], obtain the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm 3 / mol), and (ΣΔei / ΣΔvi) 0.5 as the SP value (cal / cm 3 ) 0.5 Let it be. The SP value can be controlled by the types and amounts of the monomers. To increase the SP value, for example, use a monomer with a large SP value. On the other hand, to decrease the SP value, for example, use a monomer with a small SP value.
[0086] <For silica fine particles 29 Calculation method of B and A / B by Si-solid NMR measurement> For silica fine particles 29 The Si-solid NMR measurement of silica fine particles is performed after separating the silica fine particles from the toner surface. Below, the method for separating the silica fine particles from the toner surface and 29The Si-solid-state NMR measurement method is described.
[0087] <Method for separating silica particles from the toner surface> When the silica fine particles separated from the surface of the toner are used as a measurement sample, the silica fine particles are separated from the toner by the following procedure.
[0088] Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1 g of toner to this dispersion and break up the toner clumps with a spatula or the like.
[0089] The centrifuge tube is placed in an Iwaki Sangyo KM Shaker (model: V.SX) and shaken for 20 minutes at 350 reciprocations per minute. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 3,500 rpm for 30 minutes.
[0090] After centrifugation, the toner particles are present in the top layer in the glass tube, and the silica fine particles are present in the aqueous solution in the lower layer. The aqueous solution in the lower layer is sampled and centrifuged repeatedly as necessary. After sufficient separation, the dispersion is dried and the silica fine particles are collected.
[0091] Next, the silica fine particles recovered from the toner particles 29 The Si-solid-state NMR measurement is carried out under the measurement conditions shown below. < 29 Si-NMR (solid state) measurement conditions solid 29 The DD / MAS measurement conditions for Si-NMR (solid state) are as follows. Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: DD / MAS method 29Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 180s Scan count: 2000
[0092] Also, solid 29 The CP / MAS measurement conditions for Si-NMR (solid state) are as follows. Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: CP / MAS method 29Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 5s Scan count: 15,000
[0093] After the above measurement, a plurality of silane components having different substituents and bonding groups of the silica fine particles are subjected to peak separation into the following M units, D units, T units, and Q units by curve fitting. M units: (Ri)(Rj)(Rk)SiO 1 / 2 Formula (4) D unit: (Rg)(Rh)Si(O 1 / 2 )2 formula (5) T units: RmSi(O 1 / 2 )3 formula (6) Q unit: Si(O 1 / 2 )4 formula (7) (In the formulas (4), (5), and (6), Ri, Rj, Rk, Rg, Rh, and Rm each represent an alkyl group such as a hydrocarbon group having 1 to 6 carbon atoms, a halogen atom, a hydroxyl group, an acetoxy group, or an alkoxy group bonded to a silicon atom.)
[0094] After peak separation, the integral value in D units obtained when the integral value in Q units in the CP / MAS measurement is set to 100 is defined as A, and the integral value in D units obtained when the integral value in Q units in the DD / MAS measurement is set to 100 is defined as B, and the values of B and A / B are calculated. EXAMPLES
[0095] The present disclosure will be described in more detail below with reference to Production Examples and Examples, which are not intended to limit the present disclosure in any way. Note that all parts used in the Examples are parts by mass.
[0096] <Magnetic material manufacturing> (Production of magnetic iron oxide) An aqueous solution containing ferrous hydroxide was prepared by mixing 1.00 to 1.10 equivalents of caustic soda solution relative to iron element, P2O5 in an amount equivalent to 0.15 mass% of iron element in terms of phosphorus, and SiO2 in an amount equivalent to 0.50 mass% of iron element in terms of silicon into an aqueous solution of ferrous sulfate. The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was carried out at 85°C while blowing in air, to prepare a slurry liquid containing seed crystals.
[0097] Next, add 0.01% of the original amount of alkali (sodium content of caustic soda) to this slurry. After adding an aqueous solution of ferrous sulfate so that the equivalent amount became 0.90 to 1.20, the pH of the slurry was maintained at 7.6 and an oxidation reaction was carried out while blowing in air, to obtain a slurry containing magnetic iron oxide.
[0098] (Production of silane compounds) 30 parts of iso-butyltrimethoxysilane was added dropwise to 70 parts of ion-exchanged water while stirring. The aqueous solution was then kept at pH 9.0 and temperature 45°C, and dispersed for 120 minutes at a peripheral speed of 0.46 m / s using a dispersing blade to carry out hydrolysis and condensation reactions. After the pH of the solution was adjusted to 9.0, the solution was immediately cooled to 10° C. to terminate the hydrolysis and condensation reactions, thereby obtaining an aqueous solution containing a silane compound.
[0099] (Magnetic material manufacturing) The above-mentioned magnetic iron oxide-containing slurry was dispersed with a pin mill, while 4.7 parts of the above-mentioned silane compound-containing liquid was added to 100 parts of magnetic iron oxide. At this time, the pH was kept at 9.0 and the temperature was kept at 55°C, and the dispersion was carried out for 60 minutes to proceed with hydrophobization treatment of the magnetic material. Thereafter, the above-mentioned dispersion was filtered using a filter press and washed with a large amount of water. Further, it was dried at 120°C for 2 hours, and the obtained particles were crushed and passed through a sieve with an opening of 100 μm to obtain a magnetic material with a number-average particle size of 230 nm.
[0100] <Production of Silica Microparticles 1> 100 parts of fumed silica (silica base material; spherical, manufactured by Aerosil Co., Ltd.) having a number-average particle size as shown in Table (1) was placed in a reaction vessel, and a solution of 15 parts of treatment agent 1 (average number of repeating units n=60) shown in Table (1) diluted with 100 parts of hexane was added while stirring under nitrogen purging, and the mixture was stirred at 300° C. for 120 minutes. The obtained silica microparticles were then crushed using a pin-type crusher to obtain silica microparticles 1.
[0101] <Production of Silica Particles 2-8, 11> Silica microparticles were produced in the same manner as silica microparticles 1, except that treating agent 1 and treating agent 2 were used in the amounts shown in Table (1) per 100 parts of femur silica having a number-average particle size as shown in Table (1).
[0102] <Production of Silica Particles 9 and 10> Production was carried out in the same manner as for silica microparticles 1, except that the type and parts of treating agent 1 were used as shown in Table (1) for 100 parts of fumed silica having a number-average particle size as shown in Table (1).
[0103] [Table 1]
[0104] In the table, R for treatment agents 1 and 2 1 and R 2 are R in the modified silicone oil represented by formula (B), 1 and R2 The parts of the treatment agents 1 and 2 are based on the silica base (i.e., The numbers of treatments of treatment agents 1 and 2 per 100 parts of (silica fine particles before surface treatment). n of treatment agents 1 and 2 respectively represents the value of n in the modified silicone oil represented by formula (B).
[0105] <Production of Resin A1> 100 parts of a mixture of raw material monomers other than trimellitic anhydride in the amounts shown in Table 2 below and 0.52 parts of tin di(2-ethylhexanoate) catalyst were placed in a polymerization tank equipped with a nitrogen introduction line, a dehydration line, and an agitator. Next, after the polymerization tank was filled with nitrogen, a polycondensation reaction was carried out for 6 hours while heating at 200°C. After the temperature was raised to 210°C, trimellitic anhydride was added, and the pressure in the polymerization tank was reduced to 40 kPa, after which a condensation reaction was further carried out. The acid value, weight average molecular weight Mw, and SP value (SPa) of the obtained resin were as shown in Table 2. This resin is called resin A1.
[0106] <Production of Resins A2 to A10> Resins A2 to A10 were produced by the same operation as for resin A1, using the raw material monomer charging amounts shown in Table 2 below. At that time, sequential sampling and measurement were performed, and when the desired molecular weight was reached, the polymerization reaction was stopped and the resin was taken out of the polymerization tank. The physical properties of the obtained resins are shown in Table 2 below. In addition, in the production of resin A9, bisphenol A propylene oxide 3-mol adduct and bisphenol A ethylene oxide 2-mol adduct were used as BPA in a molar ratio of 45.0 to 44.2. In the production of resin A10, bisphenol A propylene oxide 3-mol adduct and bisphenol A ethylene oxide 2-mol adduct were used as BPA in a molar ratio of 29.8 to 33.0. When BPA is not specified, bisphenol A propylene oxide 3-mol adduct was used.
[0107] [Table 2] In the table, isosorbide in the resin properties indicates the content (mass %) of monomer units in Resin A formed by polymerization of isosorbide represented by formula (A).
[0108] The abbreviations in the above table are: TPA: Terephthalic acid IPA: Isophthalic acid TMA: Trimellitic anhydride BPA: Propylene oxide or ethylene oxide adduct of bisphenol A (see above for details) EG: Ethylene glycol Shows.
[0109] <Wax 1~7> The waxes used are shown in Table 3 below. Table 3 below shows the SP values (SPw) and melting points of Waxes 1 to 7. [Table 3]
[0110] <Production of Toner Particle 1> 850 parts of 0.1 mol / L-Na3PO4 aqueous solution was added to a vessel equipped with a high-speed stirring device Clearmix (M Technique Co., Ltd.), and heated to 60°C while stirring at a rotation speed of 33 m / s. 68 parts of 1.0 mol / L-CaCl2 aqueous solution was added to the vessel, preparing an aqueous medium containing a small amount of poorly water-soluble dispersant Ca3(PO4)2.
[0111] A solution was prepared by mixing and dissolving the following materials using a propeller-type stirrer. When mixing the following materials, the rotation speed of the stirrer was set to 100 r / min. Styrene: 75.0 parts n-Butyl acrylate: 25.0 parts Resin A1: 13.0 parts ·Magnetic material: 90.0 parts Wax 1: 18.0 parts Monoazo dye iron complex (T-77: manufactured by Hodogaya Chemical Co., Ltd.): 1.0 part 1,6-Hexanediol diacrylate: 0.5 parts
[0112] The mixture was then heated to 60°C and stirred in a TK homomixer (manufactured by Primix Corporation (formerly Tokushu Kika Kogyo Co., Ltd.)) with the agitator rotation speed set to 9000 r / min to dissolve and disperse the solids. 10.0 parts of a polymerization initiator, tert-butylperoxyisopropyl monocarbonate (manufactured by Nippon Oil & Fats Co., Ltd., product name: Perbutyl I), was added and dissolved in the mixed liquid to prepare a polymerizable monomer composition. Next, the polymerizable monomer composition was added to the aqueous medium, heated to a temperature of 60° C., and then granulated for 15 minutes while rotating the Clearmix at a peripheral speed of 33 m / s. The mixture was then transferred to a propeller-type agitator and stirred at 100 rpm while reacting at 70°C for 5 hours, then heated to 85°C and reacted for another 4 hours to produce magnetic toner particles. After the polymerization reaction was completed, the suspension was cooled to room temperature. After cooling, hydrochloric acid was added to lower the pH to 2.0 or less to dissolve the inorganic fine particles. After washing with water several times, the mixture was dried at 40°C for 72 hours using a dryer, and then classified using a multi-division classifier utilizing the Coanda effect to obtain toner particles 1.
[0113] <Production of toner particles 2 to 14, 16, 17, 19 to 23, and 25 to 28> Toner particles 2 to 14, 16, 17, 19 to 23, and 25 to 28 were produced in the same manner as the production method of toner 1, except that the materials and the parts shown in Table 4 were used.
[0114] <Production of toner particles 15> 2.3 parts of tricalcium phosphate was added to 900 parts of ion-exchanged water heated to 60° C., and the mixture was stirred at 10,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain an aqueous medium. In addition, the following materials were uniformly dissolved and mixed using a propeller stirrer at 100 rpm to prepare a resin-containing monomer. Styrene 45.0 parts n-Butyl acrylate 25.0 parts ·Resin A9 4.0 parts 1,6-Hexanediol diacrylate: 0.5 parts
[0115] Furthermore, the following materials were dispersed using an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain a fine particle colorant-containing monomer. Styrene 30.0 parts CI Pigment Blue 15:3 7.4 parts Charge control agent (Bontron E-88 (Orient Chemical Co., Ltd.)) 1.0 part Wax 7: Paraffin wax HNP9 (manufactured by Nippon Seiro Co., Ltd.) 5.0 parts
[0116] Next, the fine colorant-containing monomer and the resin-containing monomer were mixed uniformly to obtain a polymerizable monomer composition, and then the polymerizable monomer composition was heated to 60°C. Next, the polymerizable monomer composition was put into the aqueous medium, and stirred at 10,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to form particles of the polymerizable monomer composition. Then, 10.0 parts of a polymerization initiator tert-butyl peroxypivalate was added thereto, and granulation was continued for 10 minutes. The mixture was then transferred to a propeller-type agitator and stirred at 100 rpm while reacting at 75°C for 5 hours, then heated to 85°C and reacted for another 5 hours. After the polymerization reaction was completed, the mixture was cooled to room temperature (25°C), hydrochloric acid was added to dissolve the calcium phosphate salt, and the mixture was filtered and washed with water to obtain wet colored particles. The wet colored particles were then dried at 40°C for 72 hours to obtain toner particles 15.
[0117] <Production of toner particles 18> (Preparation of Resin Particle Dispersion) [Preparation of Resin Particle Dispersion (1)] Terephthalic acid: 30 parts Fumaric acid: 70 parts Bisphenol A ethylene oxide 2 mole adduct: 5 parts Bisphenol A propylene oxide 3 mole adduct: 95 parts The above materials were charged into a 5-liter flask equipped with a stirrer, nitrogen inlet tube, temperature sensor, and distillation column, and the temperature was raised to 210°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature was raised to 230°C over 0.5 hours while distilling off the generated water, and the dehydration condensation reaction was continued at that temperature for 1 hour, after which the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized. 40 parts of ethyl acetate and 25 parts of 2-butanol were added to a vessel equipped with a temperature control means and a nitrogen replacement means to prepare a mixed solvent, and then 100 parts of the polyester resin was gradually added and dissolved therein. A 10% by mass aqueous ammonia solution (equivalent to 3 times the molar amount of the acid value of the resin) was then added thereto and stirred for 30 minutes. Next, the inside of the container was replaced with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was added dropwise at a rate of 2 parts / min while stirring the mixture, to carry out emulsification. After the dropwise addition was completed, the emulsion was returned to room temperature (20°C to 25°C) and bubbled with dry nitrogen for 48 hours while stirring. As a result, the contents of ethyl acetate and 2-butanol were reduced to 1,000 ppm or less, and a resin particle dispersion liquid in which resin particles having a volume average particle size of 200 nm were dispersed was obtained. Ion-exchanged water was added to the resin particle dispersion liquid to adjust the solid content to 20 mass %, to obtain a resin particle dispersion liquid (1).
[0118] (Preparation of Resin Particle Dispersion (2)) Resin particle dispersion (2) was obtained in the same manner as in preparation of the above-mentioned resin particle dispersion 1, except that Resin A1 was used instead of the polyester resin.
[0119] (Preparation of Colorant Particle Dispersion) [Preparation of Colorant Particle Dispersion] Cyan pigment CI Pigment Blue 15:3 (copper phthalocyanine, manufactured by DIC Corporation, product name: FASTOGEN BLUE LA5380): 70 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 200 parts The above materials were mixed and dispersed for 10 minutes using a homogenizer (Ultra Turrax T50 manufactured by IKA Corporation). Ion-exchanged water was added so that the solid content in the dispersion was 20% by mass, and a colorant particle dispersion (1) in which colorant particles having a volume average particle size of 190 nm were dispersed was obtained.
[0120] (Preparation of release agent particle dispersion) [Preparation of Release Agent Particle Dispersion (1)] Wax 1: 100 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (Ultra Turrax T50 manufactured by IKA), and then dispersed using a Manton-Gaulin high pressure homogenizer (manufactured by Gaulin) to obtain a release agent particle dispersion (solid content 20% by mass) in which release agent particles having a volume average particle size of 200 nm were dispersed.
[0121] (Preparation of toner particles) [Preparation of toner particles (1)] An apparatus was prepared in which a round stainless steel flask and a container A were connected by a tube pump A, and the liquid contained in the container A was sent to the flask by driving the tube pump A, and the container A and a container B were connected by a tube pump B, and the liquid contained in the container B was sent to the container A by driving the tube pump B. Then, the following operations were carried out using this apparatus.
[0122] ·Resin particle dispersion (1): 500 parts Colorant particle dispersion (1): 40 parts Anionic surfactant (TaycaPower brand BN2070M, sodium dodecylbenzenesulfonate): 2 parts The above materials were placed in a round stainless steel flask, and 0.1N nitric acid was added to adjust the pH to 3.5, after which 30 parts of an aqueous nitric acid solution with a polyaluminum chloride concentration of 10% by mass was added. The materials were then dispersed at 30°C using a homogenizer (IKA Ultra Turrax T50), and the particle size of the aggregated particles was allowed to grow while increasing the temperature in a heating oil bath at a rate of 1°C / 30 minutes.
[0123] Meanwhile, 50 parts of resin particle dispersion (2) was placed in container A of a polyester bottle, and 25 parts of release agent particle dispersion (1) was placed in container B. Next, the liquid delivery speed of tube pump A was set to 0.70 parts / minute, and the liquid delivery speed of tube pump B was set to 0.14 parts / minute. When the temperature inside the round stainless steel flask during the formation of aggregated particles reached 37.0°C, tube pumps A and B were driven to start delivering each dispersion. This allowed the release agent particle concentration to be adjusted to the following: While the temperature was being increased, the mixed dispersion in which the resin particles and the release agent particles were dispersed was transferred from container A to the round stainless steel flask in which aggregated particles were being formed. After the transfer of each dispersion liquid to the flask was completed and the temperature inside the flask reached 48° C., the flask was maintained at this temperature for 30 minutes to form secondary aggregated particles. Then, 50 parts of the resin particle dispersion (2) was slowly added and held for 1 hour, and a 0.1 N aqueous sodium hydroxide solution was added to adjust the pH to 8.5, and the mixture was heated to 85° C. with continued stirring and held for 5 hours. Then, the mixture was cooled to 20° C. at a rate of 20° C. / min. The dispersion liquid is filtered, thoroughly washed with ion-exchanged water, and dried to obtain toner particles 18.
[0124] <Production of toner particles 24> 850 parts of 0.1 mol / L-Na3PO4 aqueous solution was added to a container equipped with a high-speed stirring device Clearmix (manufactured by M Technique Co., Ltd.), and heated to 60°C while stirring at a rotation speed of 33 m / s. 68 parts of 1.0 mol / L-CaCl2 aqueous solution was added to this to prepare an aqueous medium containing a small amount of poorly water-soluble dispersant Ca3(PO4)2. In addition, a solution was prepared by mixing and dissolving the following materials using a propeller-type stirring device. When mixing the following materials, the rotation speed of the stirrer was set to 100 r / min. Styrene: 75.0 parts n-Butyl acrylate: 25.0 parts ·Magnetic material: 90.0 parts Wax 3: 18.0 parts Monoazo dye iron complex (T-77: manufactured by Hodogaya Chemical Co., Ltd.): 1.0 part 1,6-Hexanediol diacrylate: 0.5 parts
[0125] The mixture was then heated to 60°C and stirred in a TK homomixer (manufactured by Primix Corporation (formerly Tokushu Kika Kogyo Co., Ltd.)) with the agitator rotation speed set to 9000 r / min to dissolve and disperse the solids. 10.0 parts of tert-butyl peroxypivalate, a polymerization initiator, was added to the mixture and dissolved in the mixture to prepare a polymerizable monomer composition. Next, the polymerizable monomer composition was added to the aqueous medium, heated to 60°C, and then granulated for 15 minutes while rotating the Clearmix at a peripheral speed of 33 m / s. The mixture was then transferred to a propeller-type agitator and stirred at 100 rpm while reacting at 70°C for 5 hours, then heated to 85°C and reacted for another 4 hours to produce magnetic toner particles. After the polymerization reaction was completed, the suspension was cooled to room temperature. After cooling, hydrochloric acid was added to lower the pH to 2.0 or less to dissolve the inorganic fine particles. After repeated washing with water, the mixture was dried at 40°C for 72 hours using a dryer, and then classified using a multi-division classifier utilizing the Coanda effect to obtain toner particles 24. The physical properties of the toner particles are shown in Table 4.
[0126] [Table 4]
[0127] <Production of Toner 1> Toner particles 1 (100.0 parts) and silica fine particles 7 (1.0 part) were externally mixed using an FM10C (manufactured by Nippon Coke and Engineering Co., Ltd.). The external addition conditions were as follows: amount of toner particles charged: 1.8 kg, rotation speed: 3600 rpm, external addition time: 30 minutes. After that, the mixture was sieved through a mesh having an opening of 200 μm to obtain toner 1.
[0128] <Production of Toners 2 to 25 and Comparative Toners 1 to 10> Toners 2 to 25 and comparative toners 1 to 10 were obtained in the same manner as in the production of toner 1, except that the toner particles and silica fine particles were changed as shown in the table below.
[0129] [Table 5] In the table, the content of resin A is the content (mass %) in the toner particles.
[0130] (Toner Evaluation) Toners 1 to 25 and comparative toners 1 to 10 were evaluated by the following method. For the evaluation, a color laser printer (LBP-712Ci, manufactured by Canon) modified to have a process speed of 300 mm / sec was used. The toner in the cyan cartridge of the printer was removed, and 150 g of each of toners 18 and 25 was filled into this cartridge. In addition, the toner in the black cartridge of the printer was removed, and 150 g of each of toners 1 to 17, 19 to 24, and comparative toners 1 to 10 was filled into this cartridge. The above cartridges were then installed in the printer station, and the following evaluations were performed.
[0131] (Evaluation of color unevenness) At room temperature and humidity (temperature 23°C, humidity 60% RH), coated paper (OS coated paper W, manufactured by Fuji Xerox, basis weight 127 g / m 2 ) a 5 cm x 5 cm all-black image with an image area ratio of 100% for cyan toner and an image area ratio of 100% for black toner was formed, and 100 sheets were output continuously.
[0132] When black toners 1 to 17, 19 to 24 and comparative toners 1 to 10 were used, the a of the image was measured using a reflection spectrodensitometer (manufactured by X-Rite, product name: Xrite-939) for the 100th image. * value, and b * Value (CIE1976L * a * b * a in color system * value and b * The color difference ΔE between the two points with the furthest measurement values was calculated and used as an index of color unevenness. * value and b * The values are a *1 , and b *1 And then, another point a * value and b * The values are a *2 and b *2 The color difference ΔE was calculated using the following formula. ΔE=((a *1 -a *2 ) 2 +(b *1 -b *2 ) 2 ) 0.5
[0133] When cyan toners 18 and 25 were used, the L of the image was measured using a reflection spectrodensitometer (manufactured by X-Rite, product name: Xrite-939) for the 100th image. * Value, a * value, and b * Value (CIE1976L * a * b * L in color space * Value, a * value, and b* The L value of one of the above points was measured at 30 random points. The color difference ΔE between the two points with the furthest measurement values was calculated and used as an index of color unevenness. * Value, a * value, and b * The values are L *1 , a *1 , and b *1 And then another L * Value, a * value, and b * The values are L *2 , a *2 , and b *2 The color difference ΔE was calculated using the following formula. ΔE=((L *1 -L *2 ) 2 +(a *1 -a *2 ) 2 +(b *1 -b *2 ) 2 ) 0.5 It is favorable if the ΔE value is 2.0 or less, and it is more preferable that the ΔE value is 1.0 or less.
[0134] (Evaluation of fogging in a high temperature and humidity environment) In a high temperature and high humidity environment (temperature 30°C, humidity 80% RH), a horizontal line image with a printing rate of 0.2% was printed out, and an intermittent operation of pausing every two sheets was repeated to perform a printout test of 16,000 sheets. After the test was completed and the sheet was left for 48 hours, a blank image was printed out again, and the reflectance (%) of the non-image area of the obtained image was measured using a "REFLECTOMETER MODEL TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.). The obtained reflectance was subtracted from the reflectance (%) of unused printout paper (standard paper) measured in the same manner, and the value (%) was used to evaluate the image according to the following criteria. The smaller the value, the more suppressed the image fog is and the better the electrostatic property is. The evaluation was performed in gloss paper mode using gloss paper (HP Brochure Paper 200g, Glossy, manufactured by HP, 200g / m 2 ) was used. A grade of C or higher was considered to be good. (Evaluation Criteria) A: Less than 0.5% B: 0.5% or more but less than 1.5% C: 1.5% or more and less than 3.0% D: 3.0% or more
[0135] (Evaluation of low temperature fixability) The following evaluations were carried out using toners 1 to 25 and comparative toners 1 to 10. The evaluation was carried out in an environment of normal temperature and humidity (temperature 23°C, humidity 50% RH). The fixing media was FOX RIVER BOND paper (110 g / m 2 ) was used. By using a medium with relatively large surface irregularities and thick paper, the white spots described below are more likely to occur, and the low-temperature fixability can be evaluated strictly. The fixation unit was cooled to room temperature (25°C), and 100 sheets of solid black were printed continuously, and the average number of white spots in the solid black images for 95 to 100 sheets was measured. By continuously printing solid black, the heat of the fixation unit is taken away by the media, resulting in a state in which sufficient heat is not retained, which results in a strict evaluation of the low-temperature fixability of the toner. If the fixability of the toner is insufficient, a so-called white spot image in which unfixed toner is white is output. The evaluation result is judged by visually observing the average number of white spots generated in the output image using a microscope that can be magnified 10 times or more. The smaller the number, the better the low-temperature fixability of the toner. In this evaluation, the fixability performance was evaluated based on the temperature of the fixation unit at which the number of white spots is less than 10. The lower this temperature, the better the low-temperature fixability of the toner.
[0136] [Table 6]
Claims
1. A toner comprising toner particles containing a binder resin and a wax, and inorganic fine particles on the surfaces of the toner particles, The binder resin contains resin A, The SP value of the resin A calculated by the Fedors method is SPa (cal / cm 3 ) 0.5 year, The SP value of the wax calculated by the Fedors method is SPw (cal / cm 3 ) 0.5 When The SPa and the SPw satisfy the following formula (1), 2.50≦SPa−SPw≦4.50 (1) the inorganic fine particles contain silica fine particles surface-treated with silicone oil, The silica fine particles 29 In the Si-solid NMR measurement, The integral value in D units obtained when the integral value in Q units in the CP / MAS measurement is set to 100 is set to A, When the integral value of the Q unit in the DD / MAS measurement is 100, the integral value of the D unit obtained is B. The toner, wherein A and B satisfy the following formulae (2) and (3): 30≦B≦60... (2) 4.0≦A / B≦6.0 (3)
2. 2. The toner according to claim 1, wherein the resin A is a polyester resin.
3. 3. The toner according to claim 1, wherein the content of the resin A in the toner particles is 0.5% by mass or more.
4. The toner according to any one of claims 1 to 3, wherein the SPa satisfies the following formula (4): 10.50≦SPa≦12.80 (4)
5. The toner according to any one of claims 1 to 4, wherein the SPw satisfies the following formula (5): 7.90≦SPw≦9.60 (5)
6. The toner according to claim 5 , wherein the SPw satisfies the following formula (6): 7.90≦SPw≦9.20 ... (6)
7. the inorganic fine particles contain the silica fine particles, The silica fine particles are surface-treated products obtained by subjecting untreated silica fine particles to a surface treatment with the silicone oil, 7. The toner according to claim 1, wherein the amount of the silicone oil treated is 15.0 parts by mass or more and 40.0 parts by mass or less with respect to 100 parts by mass of the silica fine particles before the surface treatment.
8. The toner according to any one of claims 1 to 7, wherein the resin A has a monomer unit represented by the following formula (A):
9. The toner according to any one of claims 1 to 8, wherein the silicone oil contains a modified silicone oil.
10. The toner according to any one of claims 1 to 9, wherein the silicone oil contains a modified silicone oil represented by the following formula (B): (In the formula, R 1 R is a carbinol group, a hydroxyl group, an epoxy group, a carboxyl group, an alkyl group, or a hydrogen atom. 2 is a carbinol group, a hydroxy group, an epoxy group, a carboxy group, or a hydrogen atom. m is an integer of 30 to 200. The alkyl groups on the side chains in formula (B) may each be substituted with a carbinol group, a hydroxy group, an epoxy group, a carboxy group, or a hydrogen atom.
11. The toner according to claim 10, wherein the modified silicone oil represented by the formula (B) is a modified silicone oil represented by the following formula (C): (In the formula, p is an integer of 30 to 200.)
12. The toner according to any one of claims 9 to 11, wherein the silicone oil further contains a polydimethylsiloxane represented by the following formula (D): (In the formula, n is an integer from 30 to 200.)
13. the inorganic fine particles contain the silica fine particles, The silica fine particles are surface-treated products obtained by subjecting untreated silica fine particles to a surface treatment with the silicone oil, 13. The toner according to claim 1, wherein the number average particle size of primary particles of the silica fine particles before the surface treatment is 5 nm or more and 35 nm or less.
14. The toner according to any one of claims 1 to 13, wherein the number average particle diameter of primary particles of the silica fine particles before the surface treatment is 5 nm to 30 nm.
Citation Information
Patent Citations
Two-component developer for image formation and image forming method using the same
JP2002365843A
Hydrophobic silica particles and method for producing the same
JP2013527107A
Toner
JP2015172744A
Toner and method for manufacturing the toner
JP2017044981A
Toner
JP2019086642A